Widespread phenotypic hypervariation in the enigmatic anchialine shrimp Barbouria cubensis (Decapoda: Barbouriidae) - Ditter, Robert E.; Erdman, Robert B.; Goebel, Anna M.; Bracken-Grissom, Heather D. (Zootaxa, 2019)
Classification and evolutionary relationships among anchialine shrimp from the family Barbouriidae Christoffersen, 1987, has long been a topic of debate amongst crustacean taxonomists. To date, no study has examined morphological or molecular variation among populations of these enigmatic shrimp. The present study documents and analyzes patterns of widespread morphological variation within populations of Barbouria cubensis von Martens, 1872, from anchialine pools on three Bahamian islands. Such extensive morphological variation confounds identification using classic taxonomical methods. Phenotypic variation is by no means a new topic, but studies of decapods are typically limited to isolated individuals or few morphological characters. Moreover, past studies of B. cubensis do not report extensive morphological variation, however we find that upwards of 90% of individuals are affected. Anomalous phenotypes are described in 54 morphological characters with no detectable pattern associated with geographic distribution. The term phenotypic hypervariation (PhyV) is used to describe morphological variation that greatly deviates from any previous taxonomic descriptions.  Analysis of partial sequences of the 16S and COI mitochondrial genes confirm the identity of morphologically variable specimens as B. cubensis without population structure across the tropical western Atlantic. A test for cryptic diversity within B. cubensis suggests PhyV is not correlated with cryptic diversity. Morphological variation at this scale likely depends on recent changes either to their environment or genetic diversity.